Understanding and Monitoring Service Delivery in a Decentralizing Environment in Mongolia : The Case of Education and Health - World Bank (World Bank, Washington, DC, 2016)
The Integrated Budget Law (IBL) of 2011 has helped launch national reform toward greater decentralization, with significant implications for education and health service delivery. Building on lessons from previous phases of fiscal reform, the IBL grants new “decision space” to sub-national officials, increasing the degree of autonomy that lower levels of government, schools, and health care facilities have in delivering services. It provides local officials with significantly more discretion in how they spend education and health funds from the central government, which previously were subject to strict line item budgeting.